Rostislav I . Grigorchuk. To the 60th anniversary (Algebra and Discrete Mathematics, 2013)
On February 23, 2013, an outstanding mathematician, one of the founders of our journal Professor Rostislav I. Grigorchuk turns his 60th. The influence of Grigorchuk's famous results on the development of various branches of mathematics is difficult to overestimate and his active involvement in the international mathematics community life is pretty significant.